Аналіз та досягнення Європейської стратегії щодо інвалідності на 2010–2020 роки на першому етапі своєї реалізації - Комарова, Т.; Трагнюк, О.; Бойчук, Д. (НДІ ПЗІР НАПрН України, 2023)
Зважаючи на постійне зростання кількості осіб з інвалідністю, а також той факт, що у цієї категорії людей на 70 % більше шансів зазнати бідності, перед Європейським Союзом постало нагальне питання стосовно формування відповідної політики. Цьому також сприяло підписання Європейським Союзом Конвенції ООН про права осіб з інвалідністю (UNCRPD), яка вимагала від Європейського Союзу наявності ефективного інструментарію для повноцінної реалізації її положень. Амстердамський договір у статті 13 (нині стаття 19 Договору про функціонування ЄС) проголосив право людини не страждати від дискримінація, зокрема, на підставі інвалідності. Це стало точкою відліку на шляху до справжньої європейської політики в сфері інвалідності. Першим кроком у цьому плані стало затвердження програми дій по боротьбі з дискримінація. Згодом Європейський Союз затвердив Європейську стратегію з інвалідності на 2010–2020 роки. Стратегія визначала механізми, необхідні для реалізації Конвенції ООН про права людини з інвалідністю. В ній були виділені вісім основних сфер діяльності і для кожної з них були розроблені необхідні ключові дії, які треба було здійснити. Європейська стратегія з інвалідності на 2010–2020 роки стала ключовим інструментом Європейського Союзу для розширення можливостей людей з інвалідністю користуватися своїми правами та свободами, повною мірою брати участь у житті суспільства та функціонуванні економіки. І перегляд та оцінка цієї Стратегії підтвердили це, вказуючи на значний прогрес, досягнутий під час імплементації її положень, особливо у сфері доступності. Хоча на сьогодні затверджено нову Стратегію з інвалідності на 2021–2030 рр., аналіз результатів реалізації попередньої Стратегії залишається актуальним завданням, зважаючи на необхідність розуміння успішності її імплементації та внесення коректив відповідно до нових загроз і викликів. Problem setting. Ensuring the full participation of people with disabilities in society, combating discrimination, removing barriers and combating social exclusion are the main goals of the European Union in the field of protection of the rights of persons with disabilities. The signing of the UN Convention on the Rights of Persons with Disabilities by the European Union imposed an obligation to implement its provisions, which in turn necessitated the adoption of an instrument for the effective and full implementation of the Convention’s requirements. And European Disability Strategy 2010-2020 became such a tool. Analysis of recent researches and publications. Given the importance of this topic, the European disability policy attracts the attention of many foreign authors, including S. Charitakis, D. L. Hosking, Ch. O’Mahony, Sh. Quinlivan, L. Waddington. Among domestic lawyers, S. Vavzhenchuk, S. Maidanik, O. Melnyk, L. Susharnyk and others touched on this problem in their works. But in general, this problem remains little researched precisely in the science of international law, which gives it relevance. Target of the research is to analyze the European disability strategy 2010-2020, identify the main directions of its activities and assess the current state of implementation of relevant measures. Article’s main body. The article is devoted to the description of the state and problems of the implementation of The European Disability Strategy 2010-2020. The author provides a detailed analysis of the development and adoption process of the European Disability Strategy 2010-2020 and reveals the main goals and objectives of this document. The author also emphasizes the achievements that have been made during this stage of the implementation of the Strategy. Special attention in the paper is given to the recommendations provided by the UN Committee on the Rights of Persons with Disabilities during the review of the Strategy and the possibilities for their implementation. Сonclusions and prospects for the development. The strategy was developed in response to the significant challenges faced by people with disabilities in accessing education, employment, healthcare, and other basic services. The strategy was designed to create a barrier-free Europe by 2020, where people with disabilities could enjoy equal opportunities and participate fully in society. The author highlights the recommendations provided by the UN Committee on the Rights of Persons with Disabilities during the review of the provisions of the European Disability Strategy 20102020. The most important conclusion is that «the goals of the decade-long strategy remain fully relevant» at this stage, and it has been decided to continue implementing existing measures until the end of the Strategy’s term. It can be said that the progress made at this stage, particularly in terms of accessibility, is quite significant and allows for greater opportunities for people with disabilities to integrate and actively participate in society.
Keywords: особи з інвалідністю; дискримінація; Європейський Союз; Європейська стратегія з інвалідності на 2010-2020 рр.; persons with disabilities; discrimination; EU; European Disability Strategy 2010-2020